(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
ملخص: شهد الحوض الغربي للمتوسط طيلة الفترة الحديثة صراعا مريرا بين ضفتيه، لدوافع وأسباب عديدة، ولعل أبرز عامل غذّى هذا العداء هو العامل الديني، واستمرارية الصراع بين الهلال والصليب، وكان لأيالة الجزائر دور كبير في هذا الصراع، أو بالأحرى الطرف الثابت في تعاطي نشاط القرصنة؛ باعتبارها تمثل رأس القوة في الضفة الجنوبية من الحوض الغربي للمتوسط، مقارنة بأيالة تونس التي كان تعاطيها لهذا النشاط متقطع؛ بل وتناقص بشكل كبير مع بداية القرن الثامن عشر، والذي تزامن مع عهد الحسينيين، نظرا لجنوح البايات الحسينين للسلم مع دول غرب أوربا المتوسطية، ومن هنا أردنا البحث في أسباب انتعاش نشاط القرصنة في عهد حمّودة باشا الحسيني (1782 – 1814) ، في ظل توتر علاقاته مع فرنسا وجمهورية البندقية. وخلصت الورقة البحثية، إلى التأكيد على أن هذا النشاط ساهم في توفير مداخيل للأيالة، إلا أنه كان ظرفيا ومحتكرا من رجالات البلاط في البلاد التونسية. الكلمات الدالة: البحر الأبيض المتوسط ؛ حمودة باشا؛ الحسينيين؛ القرصنة؛ فرنسا؛ البندقية؛ الدويلات الايطالية. Abstract : The western basin of the Mediterranean witnessed a bitter conflict between the two sides during the modern era, for several motives and reasons. The most prominent factor that fed that conflict was religion and the everlasting feud between crescent and cross. It is noticeable that Algeria had a major role in this conflict, or rather was the constant part in the activity of Corsair. As Algeria is the main power in the western basin of the Mediterranean compared to Tunisia which had an interrupted activity of piracy, and it decreased a lot by the beginning of the 18th century, which coincided the Hussenians rule, regarding that Hussenians Bayas preferred peace with Eastern Europe’s Mediterranean countries. However, this did not suppress the refresh of Corsair in the reign of Hammouda Pacha, mainly because of his tense relations with France and Venice. All in all, we can say that this activity contributed in providing incomes for the country even though it was for a short period and mostly taken by high structure in Tunisia. key words: the Mediterranean; Hammouda Pasha; the Hussenians; Corsair; France; Venice; Italian states